Life style factors associated with the risk of type 2 diabetes mellitus - Shrestha, Bikash; Nepal, Bipin; Shakya, Yagya Laxmi; Regmi, Binaya (Grande Medical Journal, 2019)
Introduction: Type 2 diabetes mellitus is the commonest form of diabetes affecting more than 90% of the diabetic population worldwide. The prevalence of type 2 diabetes and its complications are increasing in the world, including developing nations like Nepal. This study aimed to determine the association between the lifestyle risk factors and the risk of type 2 diabetes mellitus in Nepalese population. Methods: This is hospital based cross sectional observational study done in the urban area of Nepal. Records of clients coming for the general health checkup in Grande International Hospital were evaluated in this study. Comparisons of the lifestyle factors in participants having and not having type 2 diabetes mellitus were done. Results: Significant associations with diagnosis of diabetes mellitus (DM) type 2 were seen in age (P ≤ 0.001), associated hypertension (P ≤ 0.001), dyslipidemia, family history of DM (P ≤ 0.001), alcohol use (P ≤ 0.001), and tobacco use (P ≤ 0.001). Logistic regression analysis showed that the odds of having diabetes were high in age group above 40 (OR – 6.9, CI 3.82 – 12.47), history of hypertension (OR- 3.84, CI 2.42 – 6.08), tobacco users (OR-2.26, CI 1.12 – 4.53), alcohol users (OR-3.99, CI 2.47 – 6.44), family history of DM (OR-2.44, CI 1.53 – 3.89), and abdominal obesity in both males (OR-3.9, CI 2 – 7.4) and females (OR-9.6, CI 3.78 – 24.35). Conclusions: The modifiable risk factors - obesity, smoking and alcohol use carry significant risks of developing type 2 diabetes. These red flag signs call for urgent attention to look for and rectify the modifiable risk factors in Nepalese population to prevent diabetes.